Analisis Likuiditas, Solvabilitas dan Arus Kas Operasi terhadap Financial Distress dengan Komite Audit sebagai Variabel Moderasi - Susilawati, Elis; Gurendrawati, Etty; Khairunnisa, Hera (LPPM Universitas Negeri Jakarta, 2023)
This research was conducted to determine the effect of liquidity, solvency, and operating cash flow on financial distress with the audit committee as a moderating variable. The purposive sampling method was used as a sampling technique with 28 selected companies from all infrastructure companies listed on the Indonesia Stock Exchange for 2020 – 2021. This research uses secondary data obtained by documentation techniques from financial statements, cash flow reports, and company annual reports. The data was processed using panel data regression analysis with the Eviews 12 program. The results of this study indicate that liquidity and operating cash flow have a significant positive effect on financial distress. Meanwhile, solvency does not affect financial distress. Then the audit committee as a moderating variable in this study is unable to moderate the effect of liquidity, operating cash flow, and solvency on financial distress.